Internet Addiction among University Students: Causes, Consequences, and the Role of Cyber Counseling - Abidoye Tiamiyu, Kamoru; Bolanle Abdulkareem, Habibat; Olabis Popola, Balikis (Universitas Komputer Indonesia, 2024)
This study explores the prevalence of internet addiction among undergraduate students in Kwara State and examines the potential effectiveness of cyber counselling in addressing this issue. The paper commences by providing a precise definition of internet addiction, proceeds to assess its prevalence among undergraduates in Kwara State, conducts an in-depth review of existing research on the factors contributing to internet addiction, and outlines the adverse consequences associated with excessive internet use among students. Based on this thorough analysis, the research emphasizes the crucial role that cyber counsellors, professionals trained to offer therapeutic guidance and support for individuals struggling with internet addiction, can play in helping individuals manage their addiction and improve their overall well-being. Furthermore, the study advocates for a collaborative approach, bringing together cyber counsellors, educational institutions, and other relevant organizations, to raise awareness about the risks of internet addiction and to develop initiatives and policies that promote a healthier and more balanced internet usage among student populations